Emerging Importance of Chemokine Receptor CXCR4 and Its Ligand in Liver Disease - Sheng Wang; Sheng Wang; Songsen Gao; Yueran Li; Xueyi Qian; Jiajie Luan; Xiongwen Lv (Frontiers in Cell and Developmental Biology, 2021)
Chemokine receptors are members of the G protein-coupled receptor superfamily, which together with chemokine ligands form chemokine networks to regulate various cellular functions, immune and physiological processes. These receptors are closely related to cell movement and thus play a vital role in several physiological and pathological processes that require regulation of cell migration. CXCR4, one of the most intensively studied chemokine receptors, is involved in many functions in addition to immune cells recruitment and plays a pivotal role in the pathogenesis of liver disease. Aberrant CXCR4 expression pattern is related to the migration and movement of liver specific cells in liver disease through its cross-talk with a variety of significant cell signaling pathways. An in-depth understanding of CXCR4-mediated signaling pathway and its role in liver disease is critical to identifying potential therapeutic strategies. Current therapeutic strategies for liver disease mainly focus on regulating the key functions of specific cells in the liver, in which the CXCR4 pathway plays a crucial role. Multiple challenges remain to be overcome in order to more effectively target CXCR4 pathway and identify novel combination therapies with existing strategies. This review emphasizes the role of CXCR4 and its important cell signaling pathways in the pathogenesis of liver disease and summarizes the targeted therapeutic studies conducted to date.